The Legal Basis for Exemption from Punishment in the Crime of Bribery - Muhammad, Mohammed Rashid Hassan; Saeed, Zana Rafeeq (Journal of Legal and Political Studies, 2015)
It is worthy to say that the crime of bribe can be considered as dishonorable crime , its worthy to mention too that the crime is affect part of corruption phenomena so that the Iraqi legislator did his best for reducing the crime by adopting legal and non legal means for that , I mean by this the legal exemption from penalty. In this research we assessed this presumption and made our legal opinion in dealing with subject like that .
Keywords: crime; dishonorable ,corruption ,phenomena